Konflik Peran Ganda Ibu dalam Pendampingan Belajar Anak Tingkat SD pada Masa Pandemi di Desa Surodakan Kabupaten Trenggalek - Amallina, Nada Afifah; Handoyo, Pambudi (Paradigma, 2023)
The COVID-19 pandemic has become a major problem globally, including in Indonesia, not only has an impact on the country's economy but the COVID-19 pandemic also has a major impact on an education system. Even global learning methods must be changed at all levels of education. The learning process, which was initially through face-to-face meetings, since the pandemic took place, the government has implemented online learning. This causes conflict in working parents who have to give a lot of time to learning assistance, especially for elementary school children. This conflict occurred in Trenggalek Regency. In terms of mentoring, most of them are done by mothers because they are closer to children and are considered more patient in accompani than fathers. The majority of mothers in Surodakan Village besides being housewives also become working women. With the role of a career woman, it will affect her role as a housewife. In addition, its role as a companion for children's learning will also affect the quality of performing other roles. Limited time to accompany children coupled with piled up work can cause conflicts in the family caused by the dual role of a mother. This research is a qualitative research with a descriptive analysis approach from Creswell. This research was conducted in Trenggalek Regency. The subjects of the study were working mothers who had elementary school children in grades one to three. Data collection is carried out by two techniques, namely primary and secondary. The data obtained will be analyzed with techniques from Miles and Heberman. There are three stages: Data reduction, data presentation, and conclusions. Data were analyzed using Nurture's gender theory perspective. The result is that the utilization of income sources obtained by working mothers is widely used to meet the economic needs of families. This working mother is proof that women are able to break out of the social construction of society, but the multi-role that is carried out ultimately gives birth to a burdensome double workload. Keywords: Double burden of Mothers, Child learning assistance, Pandemic, Trenggalek